Diversity of microcystin genotypes among populations of the filamentous cyanobacteria Planktothrix rubescens and Planktothrix agardhii - Kurmayer, Rainer (2006)
Microcystins (MCs) are toxic heptapeptides that are produced by filamentous cyanobacteria Planktothrix rubescens and P. agardhii via non-ribosomal peptide synthesis. MCs share a common structure cyclo (-D-Alanine(1)-L-X(2)- D-erythro-ß-iso-aspartic acid(3)-L-Z(4)-Adda(5)-D-Glutamate(6)- N-methyl-dehydroalanine(7)) where X(2) and Z(2) are variable L-amino acids in positions 2, 4 of the molecule. Part of the mcyB gene (1,451 bp) that is involved in the activation of the X(2) amino acid during MC synthesis was sequenced in 49 strains containing different proportions of arginine, homotyrosine, and leucine in position 2 of the MC molecule. Twenty-five genotypes were found that consisted of eight genotype groups (A-H, comprising 2-11 strains) and 17 unique genotypes. P. rubescens and P. agardhii partly consisted of the same mcyB genotypes. The occurrence of numerous putative recombination events that affected all of the genotypes can explain the conflict between taxonomy and mcyB genotype distribution. Genotypes B (homotyrosine and leucine in X(2)) and C (arginine in X(2)) showed higher nonsynonymous/synonymous (d(N)/d(S)) substitution ratios implying a relaxation of selective constraints. In contrast other genotypes (arginine, leucine, homotyrosine) showed lowest d(N)/d(S) ratios implying purifying selection. Restriction fragment length polymorphism (RFLP) revealed the unambiguous identification of mcyB genotypes, which are indicative of variable X(2) amino acids in eight populations of P. rubescens in the Alps (Austria, Germany, Switzerland). The populations were found to differ significantly in the proportion of specific genotypes and the number of genotypes that occurred over several years. It is concluded that spatial isolation might favour the genetic divergence of microcystin synthesis in Planktothrix spp.